Stereoselective Synthesis of the Key Intermediates of the HIV Protease Inhibitor Fosamprenavir and Its Diastereomer - Panov, Illia; Drabina, Pavel; Hanusek, Jiří; Sedlák, Miloš (Synlett, 2013)
Highly stereoselective Henry reaction has been used in the synthesis of the fosamprenavir precursor (2S,3R)-N-tert-butyloxycarbonyl-2-amino-3-hydroxy-1-phenyl-4-nitrobutane and its 2S,3S diasteromer from N-tert-butyloxycarbonyl-(S)-phenylalaninal and nitromethane. The complex of (2S,5R)- or (2R,5S)-5-isopropyl-5-methyl-2-(pyridine-2-yl)imidazolidine-4-one with copper(II) acetate has been used as the catalyst which provided the product with 2S,3R absolute configuration (dr = 90:10, overall yield 89%) or 2S,3S (dr = 99:1, overall yield 94%), respectively.
Keywords: aldol reaction; diastereoselectivity; HIV; homogenous catalysis; ligands